2012
DOI: 10.1039/c2lc40331e
|View full text |Cite
|
Sign up to set email alerts
|

High throughput method for prototyping three-dimensional, paper-based microfluidic devices

Abstract: This paper describes an efficient and high throughput method for fabricating three-dimensional (3D) paper-based microfluidic devices. The method avoids tedious alignment and assembly steps and eliminates a major bottleneck that has hindered the development of these types of devices. A single researcher now can prepare hundreds of devices within 1 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
93
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 20 publications
0
93
0
7
Order By: Relevance
“…Fluid can move freely in both the horizontal and vertical directions in a 3D-μPAD. Yoon groups [108,109], Costa et al [110] and Lewis et al [111] fabricated 3D-μPADs by stacking alternating layers of patterned paper and double-sided adhesive tape with holes. In the presence of H 2 O 2 generated by GOx, the HRP converts 4-AAP and N -ethyl- N -(2-hydroxy-3-sulfopropyl)-3,5-dimethylaniline sodium salt monohydrate (MAOS) from colorless compounds to a blue form, which can be visualized in the detection zone.…”
Section: Colorimetric Detection Of Glucosementioning
confidence: 99%
“…Fluid can move freely in both the horizontal and vertical directions in a 3D-μPAD. Yoon groups [108,109], Costa et al [110] and Lewis et al [111] fabricated 3D-μPADs by stacking alternating layers of patterned paper and double-sided adhesive tape with holes. In the presence of H 2 O 2 generated by GOx, the HRP converts 4-AAP and N -ethyl- N -(2-hydroxy-3-sulfopropyl)-3,5-dimethylaniline sodium salt monohydrate (MAOS) from colorless compounds to a blue form, which can be visualized in the detection zone.…”
Section: Colorimetric Detection Of Glucosementioning
confidence: 99%
“…Clamping of the paper layers can be used to achieve this, 26 or alternatively, doublesided adhesive layers can be used to stick the layers together. 16 Lewis et al 30 also demonstrated that spray adhesive can efficiently seal these devices and ensure good contact between the device layers. This technique is simple to use, low-cost and enables high-throughput production.…”
Section: Volume 111 | Number 11/12mentioning
confidence: 99%
“…While its foundations date back to the 1940s, the field of paperbased microfluidics has recently regained interest largely because paper is a very low cost material that has the intrinsic ability to pump fluids by capillary forces Dungchai et al, 2009;Fu et al, 2012;Hwang et al, 2011;Lewis et al, 2012;Martinez et al, 2010;Muller and Clegg, 1949;Nie et al, 2010). The ultimate goal of a paper-based microfluidic device is to offer pointof-care diagnostics at an unprecedented low price (≪ $1 per device) to achieve a widespread use in medicine.…”
Section: Introductionmentioning
confidence: 99%